2002
DOI: 10.1161/01.cir.0000017187.61348.95
|View full text |Cite
|
Sign up to set email alerts
|

Specific β 2 AR Blocker ICI 118,551 Actively Decreases Contraction Through a G i -Coupled Form of the β 2 AR in Myocytes From Failing Human Heart

Abstract: Background-We have observed direct (noncatecholamine-blocking) negative inotropic effects of the selective ␤ 2 -adrenoceptor (AR) antagonist ICI 118,551 in myocytes from failing human ventricle. In this study we characterize the effect in parallel in human myocytes and in myocytes from animal models where ␤ 2 ARs or G i proteins are overexpressed. Methods and Results-Enzymatically isolated, superfused ventricular myocytes were exposed to ␤AR agonists and antagonists/inverse agonists, and contraction amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 27 publications
5
68
4
Order By: Relevance
“…It has been demonstrated that the inverse agonist ICI 118,551 can activate the ␤ 2 -AR/G i pathway, resulting in a negative inotropic effect in cardiomyocytes from failing human heart or transgenic mice overexpressing ␤ 2 -AR (TG␤2) in a PTX-sensitive manner (Gong et al, 2002). To determine whether the inhibitory effects of ICI 118,551 on basal contraction is mediated by activation of the ␤ 2 -AR/G i pathway, we compared the effects of ICI 118,551 in cells expressing ␤ 2 -AR or the chimeras in the presence and absence of PTX treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the inverse agonist ICI 118,551 can activate the ␤ 2 -AR/G i pathway, resulting in a negative inotropic effect in cardiomyocytes from failing human heart or transgenic mice overexpressing ␤ 2 -AR (TG␤2) in a PTX-sensitive manner (Gong et al, 2002). To determine whether the inhibitory effects of ICI 118,551 on basal contraction is mediated by activation of the ␤ 2 -AR/G i pathway, we compared the effects of ICI 118,551 in cells expressing ␤ 2 -AR or the chimeras in the presence and absence of PTX treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Angiotensin AT 1A receptor signaling has been studied using receptors mutated in the conserved DRYXX(V/I)XXPL region of the amino terminal portion of the second intracellular loop: D125G/R126G/Y127A/M134A (AT 1 -i2m) and D125A/ R126A (DRY/AAY), which fail to activate G protein signaling but nonetheless support arrestin recruitment (Seta et al, 2002;Gá borik et al, 2003), and using the angiotensin II analog Sar 1 -Ile 4 -Ile 8 -Ang II, which antagonizes G q/11 coupling but promotes GRK phosphorylation, arrestin recruitment, and receptor endocytosis (Holloway et al, 2002). Analogous reagents for the ␤ 2 adrenergic receptor include the T68F/Y132G/Y219A mutant [␤ 2 AR(TYY)] (Shenoy et al, 2006) and a number of arrestin pathway-selective ␤ 2 receptor inverse agonists, including ICI118,551 and the clinically used drugs propranolol and carvedilol (Gong et al, 2002;Azzi et al, 2003;Wisler et al, 2007;Drake et al, 2008).…”
Section: Cardiovascular Roles Of Arrestinsmentioning
confidence: 99%
“…Thus, taken together, evidence accumulated so far makes it rather doubtful whether in human heart, β 2 AR can couple to, besides G s -protein, G i -protein. In this context, however, it is interesting to note that Gong et al (21) have found that in ventricular cardiomyocytes from patients with heart failure (who exhibit increased ventricular G i -protein activity, see below), but not in cardiomyocytes from non-failing human hearts (with normal G i -protein), the β 2 AR-antagonist ICI 118,551 exerted agonistic effects evoking direct negative inotropic effects. Whether or not β 3 AR might exist in the human heart, is also still an open question.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%